PERBANDINGAN ESTIMASI ANGGARAN BIAYA METODE AHSP 2022 DAN HSPK 2022 PADA PROYEK PEMBANGUNGAN GEDUNG UKM POLITEKNIK PU SEMARANG - Agung Sutarto; M. Faizal Ardhiansyah Arifin; Aufa Ardianto (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The Budget Plan is an important process in project planning as it forms the basis for making a price offer and estimation framework that will be used in tendering. It aims to consider the cost involved during the project implementation. The aim of this study is to determine which method is more economical in estimating the budget cost using the 2022 AHSP and 2022 HSPK methods. The research method used is a combination of observation and comparative quantitative methods. Observation was carried out through direct observation of structural work and work methods, while comparative quantitative method aims to estimate budget costs using the 2022 AHSP and 2022 HSPK methods. Based on the cost estimate, it can be concluded that the labor cost using the AHSP method is IDR 5,305,910,140 and using the HSPK method is IDR 31,967,258,039 with a difference percentage of 33.74%. The material cost using the AHSP method is IDR 30,389,347,431 and using the HSPK method is IDR 22,208,028,819 with a difference percentage of 0.49%. The budget plan using the AHSP method is IDR 31,980,611,351 and using the HSPK method is IDR 28,189,908,555 with a difference percentage of 5.24%. In this study, the result shows that the most economical budget cost estimate was obtained by using the HSPK method in the overall budget plan, as well as labor and material costs.